(untitled) (International Journal of Engineering & Extended Technologies Research (IJEETR), 2023)
Enterprises increasingly adopt AI-driven automation within SAP cloud landscapes to accelerate business processes, reduce human error, and improve scalability. However, integrating automation and AI into mission-critical SAP systems introduces unique security, compliance, and ethical risks—ranging from data leakage and privileged-access abuse to algorithmic bias and opaque decision-making that can affect financial reporting and regulatory standing. This paper presents an Ethical AI-Driven Automation Framework tailored for large-scale SAP Cloud environments that combines technical safeguards, governance controls, and ethical design principles to manage risk end-to-end. The framework integrates (1) a threat-aware architecture for automation components (infrastructure, integration middleware, and AI services); (2) identity, access, and secrets management aligned to least-privilege and separation-of-duties (SoD) within SAP roles; (3) data governance and privacy-preserving techniques (data minimization, tokenization, differential privacy patterns) for training and inference; (4) algorithmic transparency and human-in-the-loop (HITL) checkpoints for high-impact transactions; and (5) continuous assurance through automated compliance checks, audit trails, and behavioral anomaly detection. We describe design patterns and implementation practices that map to SAP Cloud Platform capabilities, common integration topologies (API, IDoc, RFC), and enterprise CI/CD pipelines. A risk taxonomy and decision matrix is provided to prioritize controls by impact and likelihood. We evaluate the framework with a realistic enterprise scenario (automated invoice posting and vendor master changes) using threat modelling, control mapping, and tabletop risk exercises; this evaluation demonstrates measurable risk reduction in access violations, data exposure vectors, and reduction in high-impact false positives through HITL policies. The framework strikes a balance between operational automation benefits and ethical responsibility, providing enterprises a practical roadmap to deploy AI automation in SAP Cloud environments while meeting security, compliance, and stakeholder-trust requirements.